Penerapan Model Pembelajaran Flipped Classroom dalam Pelajaran Geografi untuk Meningkatkan Keaktifan Siswa di SMAN 1 Batipuh - Syafitri, Gita Isma; Rianto, Slamet; Yuherman, Yuherman (UNIVERSITAS NEGERI MAKASSAR, 2023)
The background of this research is the active learning caused by the lack of students asking questions and the absence of participation in helping friends during discussions. The type of research used is quasi-experimental research. The research design used was the Pretest-Posttest Control Group Design X SMAN 1 Batipuh which was registered for the 2022 – 2023 academic year consisting of 9 classes with a total of 306 students. The sampling in this study was random sampling. The results of the study: 1) The activeness of the students in the Geography experimental class in class X.E 3 at Sman 1 Batipuh Academic Year 2022/2023, obtained an average percentage value of 80.54% which was classified as